Кваліфікаційно-дисциплінарна комісія адвокатури як суб’єкт доступу до професії адвоката - Владишевська, Вікторія Вікторівна; Владишевська, В. В.; Vladyshevska, Viktoriia V. (Одеса : Гельветика, 2019)
Конституція України закріплює право кожного на професійну правничу допомогу, делегуючи цю функцію інституту адвокатури. Для формування високоморальних та професійних представників адвокатської спільноти має суттєве значення забезпечення законності, прозорості, відкритості, рівності всіма суб’єктами та на всіх етапах доступу до адвокатської діяльності. Автором здійснено порівняльно-правове дослідження правового статусу учасників процедури набуття статусу адвоката, які наділені відповідним комплексом прав, обов’язків та повноважень щодо забезпечення та реалізації права на доступ до професії адвоката в Україні та в країнах пострадянського простору. Одним із органів адвокатського самоврядування, який безпосередньо бере участь у формуванні кадрового складу адвокатури, є кваліфікаційно-дисциплінарна комісія адвокатури. Статтю присвячено комплексному дослідженню питання місця і ролі кваліфікаційно-дисциплінарної комісії адвокатури у світлі набуття права на заняття адвокатською діяльністю. Проаналізовано чинне законодавство в частині доступу до професії адвоката, порядку організації, складання та оцінювання кваліфікаційного іспиту для набуття права на заняття адвокатською діяльністю в Україні. Метою статті є комплексне дослідження місця й ролі кваліфікаційно-дисциплінарної комісії адвокатури як суб’єкта доступу до адвокатської діяльності в Україні та аналогічних органів адвокатського самоврядування країн пострадянського простору, серед яких Азербайджанська Республіка, Російська Федерація. На основі вивчення зарубіжного досвіду автором надано пропозиції щодо вдосконалення законодавства про адвокатуру та адвокатську діяльність щодо порядку допуску до складання кваліфікаційного іспиту, складання цього іспиту та оцінювання результатів його складання для набуття права на заняття адвокатською діяльністю.

The Constitution of Ukraine enshrines everyone’s right to professional legal help by delegating this function to the institute of advocacy. It is important to ensure the legality, transparency, openness, equality of all the entities and at all stages of access to advocacy to form high-moral and professional representatives of the advocacy community. The author carried out a comparative legal study of the legal status of participants of the procedure of obtaining the status of a lawyer, who are endowed with an appropriate set of rights, duties and powers to secure and exercise the right to access the lawyer’s profession in Ukraine and in the countries of the former Soviet Union. One of the bodies of attorney selfgovernment, which is directly involved in the formation of the staff of the Bar, is the Qualification and Disciplinary commission of the Bar. Thus, the article is devoted to a comprehensive study of the issue of the place and role of the qualification and disciplinary commission of the Bar in the light of the acquisition of the right to practice law. The current legislation is analyzed in terms of access to the profession of lawyer, procedure of organization, conducting and passing the qualification exam for obtaining the right to practice law in Ukraine. The purpose of the article is a comprehensive study of the place and role of the qualification and disciplinary commission of the Bar, as a subject of access to advocacy in Ukraine and similar bodies of attorney selfgovernment in the countries of the former Soviet Union, including: Azerbaijan Republic, Russian Federation. On the basis of studying foreign experience, the author has proposed propositions to improve the legislation on the Bar and Practice of Law, in particular: the procedure for the admission to taking the qualification exam, passing this exam for the person who intends to become an attorney. The article is devoted to a comprehensive study of the issue of the place and role of the QualificationDisciplinary Commission of the Bar in the context of acquiring of right to practice law in terms of access to the profession of a lawyer, the procedure for admission, passage and evaluation of the qualification exam to obtain the right to engage in advocacy in Ukraine. The author analyzed the current legislation, foreign experience and made suggestions for improving the legislation on the Bar and Practice of Law.
Владишевська В. В. Кваліфікаційно-дисциплінарна комісія адвокатури як суб’єкт доступу до професії адвоката / В. В. Владишевська // Юридичний вісник. - Одеса : Гельветика - 2019. - № 3. - С. 38-43.
Keywords: набуття права на заняття адвокатською діяльністю; кваліфікаційно-дисциплінарна комісія адвокатури; кваліфікаційний іспит; доступ до адвокатської діяльності; органи адвокатського самоврядування; acquisition of the right to engage in advocacy; the Qualification and Disciplinary Commission of the Bar; qualification exam; access to advocacy; the bodies of attorney self-government; Research Subject Categories::LAW/JURISPRUDENCE